The effect of coronary stent policies on the risk of percutaneous coronary intervention among acute coronary syndrome patients in Shanghai: Real-world evidence. - Zhenyi Shao; Dongzhe Lu; Yue Wang; Di Xue (PLoS ONE)
Objective This study aimed to analyze the effect of coronary stent policies implemented in Shanghai on the risk of percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS) inpatients based on real-world data. Methods Two retrospective cohorts of inpatients with a first diagnosis of ACS who had undergone PCI for the first time in the previous year in Shanghai hospitals were examined (one for the postpolicy period and the other for the prepolicy period). χ2 tests were used to compare categorical variables between the two cohorts. Single- and multivariate Cox proportional hazards models were used to compare the risk of major adverse cardiovascular events (MACEs) between the two cohorts. Results A total of 31,760 ACS patients were included in this study. The proportion of ACS inpatients who had at least one bid-winning stent and 3 or more coronary stents implanted for first-time PCI in the postpolicy cohort was higher than that in the prepolicy cohort (86.52% vs. 55.67% and 6.27% vs. 4.39%, respectively; all p values < 0.0001). The single- and multivariate Cox proportional hazards models revealed that the unadjusted and adjusted hazard ratios for MACEs at 1 year after PCI for the postpolicy cohort relative to the prepolicy cohort were 0.869 (P<0.0001) and 0.814 (P = 0.0007), respectively. Conclusions The implementation of coronary stent policies changed coronary stent utilization but had no significant adverse effects on the risk of PCI among ACS patients in Shanghai in the short term. However, the reasons for changes in the number of coronary stents implanted should be analyzed and addressed in the future.